Right posterior sector graft via pure laparoscopic donor hepatectomy: a video presentation - Makki, Kausar; Qaleem, Mohd; Ghosh, Nalini Kanta; Yadav, Yogesh; Karan, Tathagata; Srivastava, Piyush; Agarwal, Anil; Vij, Vivek (Journal of minimally invasive surgery, 2025)
Right posterior segment graft (RPSG) in cases of living donor hepatectomy expands the donor pool; however, obtaining RPSG laparoscopically makes the procedure technically challenging. The first pure laparoscopic RPSG was performed in 2021, and since then, only a few cases have been reported in the literature. We herewith elaborate on our technique of laparoscopic RPSG, which is the first case to be reported from India. A 30-year-old surgically fit gentleman was planned for RPSG given the low future liver remnant for the modified right lobe graft (25.9%). Details of the surgical steps were being described in the supplementary video. The duration of surgery was 630 minutes, and blood loss was 750 mL (bleeding from a slipped clip). He was discharged in a stable condition on postoperative day 7. Laparoscopic RPSG is challenging yet feasible.